Influence of career mentoring on career orientation and career engagement of rural secondary school librarians - Eseadi, Chiedu (Universitas Negeri Padang, 2022)
As a career development tool, career mentoring is an important way to gain new skills, knowledge, competence, and other resources from an experienced colleague who is in the same profession. This study examined how career mentoring influences career orientation and career engagement among Nigerian rural secondary school librarians. This quantitative study gathered data from 42 librarians at selected rural secondary schools. Career mentoring significantly influences career orientation and career engagement of librarians, according to the results. A positive relationship was observed between career mentoring experience and career orientation and engagement as well as job skills among librarians. Additionally, career orientation and career engagement were shown to be significantly correlated with one another and with librarian job skills. Consequently, it is recommended that school librarians' career advancement be promoted through the development and implementation of a career mentoring program.